The efficacy of personal initiative training for academic and career success as a stress management intervention for university students - Samuels, Huyaam (Organisational Psychology, 2026)
University students face significant stress due to academic, financial, and personal pressures, particularly in South Africa, where socioeconomic instability and limited mental health resources exacerbate these challenges. While wellness programs exist, they often fail to equip students with proactive coping strategies for long-term stress management. This study explores Personal Initiative (PI) training as a potential intervention, arguing that fostering a self-starting, future-oriented mindset may enhance stress resilience. Grounded in Action Regulation Theory and the Transactional Model of Stress, this study examines whether PI training reduces perceived distress and increases self-efficacy among university students. A quantitative experimental time-series design was used, with N = 60 students initially recruited and N = 25 completing both time points. Participants were randomly assigned to an experimental group, which received a three-day PI training, or a waitlist control group. They completed the Situational Judgment Test for Personal Initiative (SJT-PI) and the Perceived Stress Scale (PSS-10) before and after training. Data were analysed using Spearman's rho correlations to examine relationships between variables, Wilcoxon Signed-Rank Tests to assess within-group changes, and moderation analysis to determine whether self-efficacy influenced the relationship between PI and perceived distress. Results indicated that PI training led to significant reductions in perceived distress and higher self-efficacy. Additionally, self- efficacy moderated the relationship between PI and stress reduction, with stronger effects observed in students with higher initial self-efficacy. These findings suggest that PI training fosters proactive coping strategies, equipping students with essential skills to navigate academic stressors. Study limitations and recommendations for future research are discussed, followed by outlining theoretical and practical implications for higher education interventions.